Analisis SWOT dalam Mengembangkan UMKM Food and Beverage di Kelurahan Keputih - Irma Nur Hanifa; Djuliandhika Rachmanigtyas; Asnanda Fairuz Tsuraya (Universitas 17 Agustus 1945 Semarang, 2023)
SWOT analysis is an analysis that has an important influence on the sustainability of a business or product, with a SWOT, business actors can consider a more mature strategy for the business to continue to run smoothly in the long term. This study aims to determine the strengths, weaknesses, opportunities and threats of MSMEs in Keputih so that the 74 Thematic KKN Groups and MSME actors can work together and work together on what must be done so that MSMEs can develop.